Low-Temperature Combustion Synthesis of a Spinel NiCo2O4 Hole Transport Layer for Perovskite Photovoltaics - Papadas, Ioannis T.; Ioakeimidis, Apostolos; Armatas, Gerasimos S.; Choulis, Stelios A. (My University, 2018)
The synthesis and characterization of low-temperature solution-processable monodispersed nickel cobaltite (NiCo 2 O 4 ) nanoparticles (NPs) via a combustion synthesis is reported using tartaric acid as fuel and the performance as a hole transport layer (HTL) for perovskite solar cells (PVSCs) is demonstrated. NiCo 2 O 4 is a p-type semiconductor consisting of environmentally friendly, abundant elements and higher conductivity compared to NiO. It is shown that the combustion synthesis of spinel NiCo 2 O 4 using tartaric acid as fuel can be used to control the NPs size and provide smooth, compact, and homogeneous functional HTLs processed by blade coating. Study of PVSCs with different NiCo 2 O 4 thickness as HTL reveals a difference on hole extraction efficiency, and for 15 nm, optimized thickness enhanced hole carrier collection is achieved. As a result, p-i-n structure of PVSCs with 15 nm NiCo 2 O 4 HTLs shows reliable performance and power conversion efficiency values in the range of 15.5% with negligible hysteresis.
Keywords: Combustion synthesis; Hole transporting layers; NiCo2O4; Perovskites solar cells; Transparent conductive oxides